2003
DOI: 10.1097/00002030-200303070-00002
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease is partly responsible for the HIV-1 inhibitory effect activated by HLA alloantigen recognition

Abstract: These findings indicate that the majority of the soluble HIV-1 inhibitory activity contained in the supernatants of mixed lymphocyte reactions is due to EDN or a closely related RNase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 17 publications
2
82
0
Order By: Relevance
“…8B) demonstrated that upon treatment by a combination of TNF-␣ and LPS for 2 h, macrophage began to secrete EDN into the culture supernatant, which peaked at 8 h. The EDN protein appeared as two bands of ϳ31 and 37 kDa, which were larger than the size of rEDN (17.5 kDa, without glycosylation). The appearance of two bands larger than the rEDN was due presumably to differential glycosylation of EDN because, using the same polyclonal antiserum, Rugeles et al (25) also found that EDN generated by cultured human PBMC appears on a SDS-PAGE gel as bands of 31-40 kDa. Therefore, EDN expression by macrophages can be rapidly induced.…”
Section: Edn Expression By Macrophages Is Induciblementioning
confidence: 98%
See 1 more Smart Citation
“…8B) demonstrated that upon treatment by a combination of TNF-␣ and LPS for 2 h, macrophage began to secrete EDN into the culture supernatant, which peaked at 8 h. The EDN protein appeared as two bands of ϳ31 and 37 kDa, which were larger than the size of rEDN (17.5 kDa, without glycosylation). The appearance of two bands larger than the rEDN was due presumably to differential glycosylation of EDN because, using the same polyclonal antiserum, Rugeles et al (25) also found that EDN generated by cultured human PBMC appears on a SDS-PAGE gel as bands of 31-40 kDa. Therefore, EDN expression by macrophages can be rapidly induced.…”
Section: Edn Expression By Macrophages Is Induciblementioning
confidence: 98%
“…In addition, EDN has also been shown to be responsible in part for the anti-HIV-1 activity found in the supernatant of MLCs (25).…”
mentioning
confidence: 99%
“…90 Other factors, such as ribonucleases may also have antiviral activity. 91 Overall, anti-X4 viruses CAF has yet to be accounted for. The importance of these factors and others to be discovered is clear and it is straightforward to envision how through gene therapy one could endogenously express them in naturally nonproducing cells.…”
Section: Prospectsmentioning
confidence: 99%
“…Furthermore, an exploration of complementary substitutions occurring during the evolution of EDN gene duplication at the divergence of the New World monkey lineages through the higher primates suggests that augmented ribonuclease activity and enhanced ribonuclease activity have developed coincidentally [35]. EDN also has activity against human immunodeficiency virus in vitro when tested in similar tissue-culture based assay systems [36][37][38]. Although the antiviral activity of the mouse eosinophil-associated ribonucleases has not been evaluated as clearly, eosinophils augment hRSV clearance in a mouse model, and can respond directly to hRSV by up-regulating mRNA encoding mouse eosinophil-associated RNases 1 and 2 [39].…”
Section: Edn Reduces Virus Infectivitymentioning
confidence: 99%